Effect of water absorption on the mechanical properties of cotton fabric-reinforced geopolymer composites - Alomayri, T.; Assaedi, H.; Shaikh, Faiz; Low, It Meng (ELSEVIER, 2014)
Cotton fabric (CF) reinforced geopolymer composites are fabricated with fibre loadings of 4.5, 6.2 and 8.3 wt%. Results show that flexural strength, flexural modulus, impact strength, hardness and fracture toughness are increased as the fibre content increased. The ultimate mechanical properties were achieved with a fibre content of 8.3 wt%. The effect of water absorption on mechanical and physical properties of CF reinforced geopolymer composites is also investigated. The magnitude of maximum water uptake and diffusion coefficient is increased with an increase in fibre content. Flexural strength, modulus, impact strength, hardness and fracture toughness values are decreased as a result of water absorption. Scanning electron microscopy (SEM) is used to characterise the microstructure and failure mechanisms of dry and wet cotton fibre reinforced geopolymer composites.